Research Trends and opportunities of augmented reality applications in architecture, engineering, and construction - Chi, Hung-Lin; Kang, Shih-Chung; Wang, Xiangyu (Elsevier BV, 2013)
Augmented reality (AR), a state-of-the-art technology for superimposing information onto the real world, has recently started to affect our daily lives. AR applications are becoming mature and versatile. This paper discusses trends in AR applications for architecture, engineering, construction, and facility management (AEC/FM). This paper specifically focuses on four technologies—localization, natural user interface (NUI), cloud computing, and mobile devices— which have the potential to influence the development of AR applications. Advances in localization technology will enable the deployment of AR in a complex environment. An NUI provides more convenient and intuitive user experiences, which can increase the usability of AR. Cloud computing environments allow users with internet access to ubiquitously retrieve information from almost anywhere. Hence, cloud computing increases the freedom of using AR in AEC/FM applications. Another factor that will lead to the wider usage of AR is that mobile devices are becoming smaller, more powerful, and less expensive. This paper summarizes the results of 101 research efforts, and outlines the research trends and opportunities for applying AR in the fields of AEC/FM.